Loss of β Epithelial Sodium Channel Function in Meibomian Glands Produces Pseudohypoaldosteronism 1–Like Ocular Disease in Mice - Yu, Dongfang; Saini, Yogesh; Chen, Gang; Ghio, Andrew J.; Dang, Hong; Burns, Kimberlie A.; Wang, Yang; Davis, Richard M.; Randell, Scott H.; Esther, Charles R.; Paulsen, Friedrich; Boucher, Richard C. (The American journal of pathology, 2018)
Human subjects with pseudohypoaldosteronism-1 because of loss-of-function mutations in epithelial sodium channel (ENaC) subunits exhibit meibomian gland (MG) dysfunction. A conditional βENaC MG knockout (KO) mouse model was generated to elucidate the pathogenesis of absent ENaC function in the MG and associated ocular surface disease. βENaC MG KO mice exhibited a striking age-dependent, female-predominant MG dysfunction phenotype, with white toothpaste–like secretions observed obstructing MG orifices at 7 weeks of age. There were compensatory increases in tear production but higher tear sodium and indexes of mucin concentration in βENaC MG KO mice. Histologically, MG acinar atrophy was observed with ductal enlargement and ductal epithelial hyperstratification. Inflammatory cell infiltration was observed in both MG and conjunctiva of βENaC MG KO mice. In older βENaC MG KO mice (5 to 11 months), significant ocular surface pathologies were noted, including corneal opacification, ulceration, neovascularization, and ectasia. Inflammation in MG and conjunctiva was confirmed by increased cytokine gene and protein expression and positive Ly-6B.2 immunostaining. Cell proliferation assays revealed lower proliferation rates of MG cells derived from βENaC MG KO than control mice, suggesting that βENaC plays a role in cell renewal of mouse MG. Loss of βENaC function resulted in MG disease and severe ocular surface damage that phenocopied aspects of human pseudohypoaldosteronism-1 MG disease and was sex dependent.